Gypsum and pressmud amelioration improve soil organic carbon storage and stability in sodic agroecosystems. (8th August 2021) - Basak, Nirmalendu; Sheoran, Parvender; Sharma, Raman; Yadav, Rajender Kumar; Singh, Ranjay K.; Kumar, Satyendra; Krishnamurthy, Thimmappa; Sharma, Parbodh C.
Abstract: Salinity–induced land degradation poses a threat to environment and food production globally. Farmers' participatory research (2014–18) was carried out to assess the potential of gypsum (Gyp) and pressmud (PM) in alleviating the sodicity stress, and improvement in soil organic carbon (SOC) pools and its stability in the Trans Indo–Gangetic Plains of India. Intensive rice–wheat cultivation using alkali water increased soil pH, exchangeable sodium percentage (ESP), and bulk density (BD) causing a net depletion in SOC. Gypsum (supplies soluble Ca 2+ ) and pressmud (mobilizes native CaCO3 ) mediated amelioration (Gyp + PM) significantly decreased soil sodification and compaction, and improved total organic carbon (TOC; 32%–64%) over the unamended control. Higher left–over C for SOC stabilization, crop biomass, and rhizodeposition returned through Gyp + PM significantly improved SOC pools and C sequestration culminating in 25% yield superiority over the unamended control. Within SOC pools, highest proportion was equally retained in very labile and non–labile C pools. On average, the passive pool contained 45% of TOC; albeit to a greater contribution through PM followed by Gyp + PM and Gyp. Rice–wheat system yield (RWSY) was positively correlated with SOC pools and indices while negatively correlated with soil pH, ESP, BD, CaCO3, and recalcitrant index. Multiple regression analysis showed stratification ratio, CaCO3, sensitivity index, and BD as key variables for yield prediction under the existing levels of soil sodicity. The key insights suggest ecosystem‐based approach using Gyp + PM in restoring the degraded lands, enhancing crop resilience and system (SOC enrichment and storage) stability, and achieving UN–Sustainable Development Goals related to food security and land degradation neutrality.